Bamboo for climate resilience: green gold of ecosystems in the UN SDG Framework - Mandaliya, Viralkumar B. (Frontiers in Ecology and Evolution, 2026)
BackgroundBamboo is a strategic resource for poverty alleviation, rural growth, ecological restoration, sustainable jobs, and industrial innovations. The function of bamboo goes beyond conventional uses and extends to the international policy reformation toward sustainable transitions. Its alignment with the United Nations Sustainable Development Goals (SDG) has been increasingly recognized.AimThis article aimed to assess bamboo for qualitative and quantitative attainment of the 169 targets of the 17 goals of the UN SDG Framework.MethodologyThe qualitative assessment was classified into three grades: high, medium, and low. The quantitative assessment examined the individual 169 targets on a scale of 1–10.Key findingsThe average percent score (APS) from the qualitative assessment of bamboo was ranked and graded for SDGs 1–17 into five major groups: group A—with APS above 50%, targets achieved (SDGs 7, 13, 1, 11, and 9); group B—with APS 40%–50%, challenges remain (SDGs 12, 6, 15, and 2); group C—with APS 30%–40%, significant challenges (SDGs 4, 5, 8, and 10); group D—with APS 15%–30%, major challenges (SDGs 17, 14, and 3); and group E—with APS below 15%, not achieved (SDG 16). Subsequently, quantitative assessment of each of the 169 UN SDG target achieved by bamboo showed that 45 targets achieved the highest scale of 8–10, 35 medium (on a scale of 4–7), 25 low (on a scale of 1–3), and 64 no connection (on a scale of 0). The highest score of 10 was shown for four targets, i.e., 8.4 (efficiency of resources and circular production), 9.2 (green industrialization, composites, and textiles), 11.6 (minimize city environmental footprint and waste), and 15.3 (land degradation neutrality through revegetation and biochar).Case studies and policy implicationsThis article further delved into case studies on bamboo for sustainability from nine countries. Based on these case studies, we derived a seven-point policy intervention integrating the UN SDG Framework for bamboo as the green gold of ecosystems.ConclusionsIn a nutshell, this article could be the first of its kind to quantify the 169 targets for bamboo on a scale of 1–10. This article provides a comprehensive review for policymakers, industries, and researchers for the integration of bamboo into climate-resilient strategies aligned with global sustainability goals.